Misdiagnosis of malignant gastrointestinal neuroectodermal tumor as Ewing sarcoma: A case report with molecular insights - Shamsuddin, Fatima; George, Smiley Annie (Indian Journal of Case Reports, 2025)
Malignant gastrointestinal neuroectodermal tumor (GNET) is a rare and aggressive mesenchymal tumor that primarily affects the gastrointestinal tract (GIT). Previously termed clear cell sarcoma (CCS)-like tumor of the GIT, GNET is histopathologically distinct from CCS and lacks melanocytic differentiation. This report details a case of a 45-year-old male who was initially misdiagnosed with Ewing sarcoma based on a core biopsy but was later confirmed to have malignant GNET following surgical intervention and molecular testing. The patient presented with abdominal pain, weight loss, vomiting, and constipation. Imaging revealed a 7.0 cm intra-peritoneal soft-tissue mass with adjacent small bowel involvement. Initial biopsy results suggested Ewing sarcoma, leading to chemotherapy treatment. However, persistent intestinal thickening and hepatic nodular lesions prompted surgical re-evaluation. Histopathological examination of the resected specimen showed sheets of tumor cells infiltrating the mucosa, submucosa, muscularis, and serosa, with extensive necrosis and high mitotic activity. Immunohistochemical analysis demonstrated positivity for S100 protein, SOX10, CD56, synaptophysin, and vimentin while being negative for HMB45, Melan-A, desmin, and CD117. Fluorescence in situ hybridization confirmed an EWSR1:CREB1 fusion, confirming the diagnosis of malignant GNET. This case underscores the importance of comprehensive histopathological and molecular assessments to ensure accurate diagnosis and optimal management of rare GI tumors like GNET. Further research is necessary to establish effective targeted therapies and improve patient outcomes.